Information Sale and Competition - Bimpikis, Kostas; Crapis, Davide; Tahbaz-Salehi, Alireza (Management Science, 2019)
This paper studies the strategic interaction between a monopolistic seller of an information product and a set of potential buyers that compete in a downstream market. The setting is motivated by information markets in which (i) sellers have the ability to offer information products of different qualities and (ii) the information product provides potential buyers not only with more precise information about the fundamentals, but also with a coordination device that can be used in their strategic interactions with their competitors. Our results illustrate that the nature and intensity of competition among the information provider’s customers play first-order roles in determining the information provider’s optimal strategy. We show that when the customers view their actions as strategic complements, the provider finds it optimal to offer the most accurate information at the provider’s disposal to all potential customers. In contrast, when buyers view their actions as strategic substitutes, the provider maximizes the provider’s profits by either (i) restricting the overall supply of the information product or (ii) distorting its content by offering a product of inferior quality. We also establish that the provider’s incentive to restrict the supply or quality of information provided to the downstream market intensifies in the presence of information leakage. The online appendix is available at https://doi.org/10.1287/mnsc.2018.3068 . This paper was accepted by Gad Allon, operations management.